The influence of neuropsychological processes in children with dyslexia that are learning to read (Research, Society and Development, 2021)
The objective of the article is to describe how the processes of this neuropsychological influence the learning of reading of children with dyslexia, from a literature review on the subject. Along this path, various socioenvironmental influences related to specific difficulties in learning to read are examined, such as the education system and the social-family context. Thus, the work contributes academically to the understanding of the disorder, showing how biological, cognitive and social aspects interfere in the dyslexia process and emphasizing how a successful intervention depends on a careful and multidimensional evaluation of these factors related to developmental dyslexias.